Perforated meckel's diverticulum presenting as a hematocele on scrotal sonography. Issue 4 (10th August 2012) - Kwait, Dylan C.; Nazarenko, Anna; Derman, Anna; Lui, Paul
Abstract Hemorrhage from ectopic gastric mucosa is the most common presenting symptom of Meckel's diverticulum. Diverticular perforation, although rare, is a potentially life‐threatening complication. Various imaging modalities can aid in the preoperative detection of Meckel's diverticulum. We report the sonographic findings of a hematocele as the heralding sequela of a perforated Meckel's diverticulum in an 11‐month‐old boy. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound, 2013